Enhancer functions and in vitro protein binding of native and mutated interferon-responsive sequences. - Cohen, B (1989)
Mutants of the Interferon responsive sequence (IRS) of the mouse and human (2'-5') A synthetase (moE-IRS and hE-IRS) were tested for their Interferon (IFN)-inducible enhancer functions and for protein binding in vitro. Two complexes R1 and R3, were formed specifically with the hE-IRS. R3 migrated much faster and was about ten times more abundant than R1. R1 and R3 are increased about 2-fold in IFN-treated HeLa extracts relatively to extracts from non-treated cells. R1 and R3 seem to involve the same DNA sequence in the probe since they react identically to competitors. Two proteins of 69 and 46 kDa form the IRS specific complexes as revealed by UV cross-linking. Identical DNA probes bearing either the hE-IRS or moE-IRS form complexes of different characteristics with nuclear proteins, suggesting that the two IRS variants are the targets of binding of different proteins or of different protein complexes.